DEVELOPMENT OF SKILLS IN INDEPENDENT CLASSES - Andrianov, V.Ye.; Andrianov, T.V.; Marchyk, V.I. (Pedagogy of Higher and Secondary Education, 2008)
The article deals with the methodical modes of development and perfection of students’ dexterity during independent training.